Factory wage structures and national agreements - "Robertson, D.J." (Cambridge, 1960)
Originally published in 1960, this book contains a survey of the structure of factory wages in Great Britain. Three case studies from engineering and shipbuilding lead into a general discussion of wage structures in these industries. The text considers the uses and abuses of systems of payment by results, particularly their effects on relative payments to different grades of workers. Overtime payments are similarly considered, especially their attraction to workers and their cost to management. Finally, the effects of these components of the pay packet are discussed in relation to the attitudes of trade unions and management, and to wage policies and theories. This book will be of value to anyone with an interest in British economic history and labour relations.
Keywords: Economics